Outcome in dogs with advanced (stage 3b) anal sac gland carcinoma treated with surgery or hypofractionated radiation therapy. (9th June 2016) - Meier, V.; Polton, G.; Cancedda, S.; Roos, M.; Laganga, P.; Emmerson, T.; Rohrer Bley, C.
Abstract: Stage 3b anal sac gland carcinoma (ASGC) can be life‐threatening. A surgical approach is not always possible or may be declined. Dogs with stage 3b ASGC treated with surgery or conformal radiation therapy (RT) with 8 × 3.8 Gy (total dose 30.4 Gy, over 2.5 weeks) were retrospectively evaluated. Patient characteristics, median progression‐free interval (PFI) and median survival time (MST) were compared. Twenty‐eight dogs were included; 15 underwent surgery, 13 underwent RT. At the time of presentation, 21% showed life‐threatening obstipation and 25% showed hypercalcaemia. PFI and MST for surgery cases were 159 days (95% CI: 135–184 days) and 182 days (95% CI: 146–218 days), both significantly lower than for RT cases with 347 days (95% CI: 240–454 days) and 447 days (95% CI: 222–672 days), ( P = 0.01, P = 0.019). Surgery as well as RT led to a fast relief of symptoms. PFI and survival of surgical patients were significantly inferior to that of a comparable patient group treated with conformal hypofractionated RT.